A Bio-assessment of DNA damage by Alkaline Comet Assay in metal workers of Kano metropolis, Nigeria. (2016) - Sani, Ali; Abdullahi, Ibrahim Lawal
Abstract: Metallic work is one of the widespread economic activities in urban Kano. Little or no attention is usually directed at occupational health risk by local or state authorities in Kano. The present work was aimed at the evaluation of DNA damage in metal workers by Alkaline Comet Assay in blood lymphocytes. The results showed that there was significant difference statistically between the level of DNA damage in blood lymphocytes of metal workers and control group (p < 0.05). In addition, the level of damage to DNA in blood of subjects with long term exposure and old age is of serious concern. There is the need to monitor occupational activities that can pose serious health risks. The relative ignorance of the metal workers about the health risks they are exposed to as well as the public should be addressed.